Food crop production, nutrient availability, and nutrient intakes in Bangladesh: Exploring the agriculture–nutrition nexus with the 2010 Household Income and Expenditure Survey - Fiedler, John L. (SAGE Publications, 2014)
Systematic collection of national agricultural data has been neglected in many low- and middle-income countries for the past 20 years. Commonly conducted nationally representative household surveys collect substantial quantities of highly underutilized food crop production data.To demonstrate the potential usefulness of commonly available household survey databases for analyzing the agriculture—nutrition nexus.Using household data from the 2010 Bangladesh Household Income and Expenditure Survey, the role and significance of crop selection, area planted, yield, nutrient production, and the disposition of 34 food crops in affecting the adequacy of farming households' nutrient availability and nutrient intake status are explored. The adequacy of each farming household's available energy, vitamin A, calcium, iron, and zinc and households' apparent intakes and intake adequacies are estimated. Each household's total apparent nutrient intake adequacies are estimated, taking into account the amount of each crop that households consume from their own production, together with food purchased or obtained from other sources.Even though rice contains relatively small amounts of micronutrients, has relatively low nutrient density, and is a relatively poor source of nutrients compared with what other crops can produce on a given tract of land, because so much rice is produced in Bangladesh, it is the source of 90% of the total available energy, 85% of the zinc, 67% of the calcium, and 55% of the iron produced by the agricultural sector. The domination of agriculture and diet by rice is a major constraint to improving nutrition in Bangladesh. Simple examples of how minor changes in the five most common cropping patterns could improve farming households' nutritional status are provided.Household surveys' agricultural modules can provide a useful tool for better understanding national nutrient production realities and possibilities.